2022
DOI: 10.32598/sija.2022.2850.3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Elder Abuse by Family Members and its Related Factors in Gonabad, Iran

Abstract: Objectives Elder abuse is one of the major social health problems in communities which has significant effects on decreasing their health and safety. The present study aims to investigate the prevalence of elder abuse by family members and its related factors in Gonabad, Iran. Methods & Materials This analytical cross-sectional study was conducted in 2020 on 401 elderly people in Gonabad, Iran. Who were selected using cluster random sampling. Data collection tools were a two-part questionnaire including a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…Other studies confirmed that a low education level was a risk factor for increased incidence of EA. 47 , 75 , 85 , 87 , 90 - 91 This finding is not consistent with those of other studies. 44 , 89 This may be because educational level is important for promoting health behaviors, seeking social support, obtaining rights, and stating opinions.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…Other studies confirmed that a low education level was a risk factor for increased incidence of EA. 47 , 75 , 85 , 87 , 90 - 91 This finding is not consistent with those of other studies. 44 , 89 This may be because educational level is important for promoting health behaviors, seeking social support, obtaining rights, and stating opinions.…”
Section: Discussioncontrasting
confidence: 87%
“…This result is consistent with the findings of other studies showing that the lower the older people's income/the less skilled the individual is, the more EA occurs. 87,91 The illiterate older people experienced caregiver abuse in the family more than their educated counterparts. Other studies confirmed that a low education level was a risk factor for increased incidence of EA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent articles from various regions in Iran indicate prevalence rates of elder abuse at 78% (10), 44.6% (11), 75.4% (12), and 55.2% (13). Recognizing the importance of the elderly population and their significant impact on society, particularly as our population ages, prompted our study design to address the lack of data on elder abuse in Isfahan.…”
mentioning
confidence: 99%